Tuning the selectivity of CO2 hydrogenation using ceramic hollow fiber catalytic modules - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Kharul, Ulhas K.; Naidu, V. Satyam; Devi, R. Nandini (Reaction Chemistry & Engineering, 2021)
The unique structural features and advantageous pore distributions of alumina hollow fibers can be exploited to tune the selectivity in heterogeneous catalysis. Formation of a finger-like cavity structure is the unique characteristic of the phase inversion method, which provides a larger surface area to volume ratio desirable for catalytic reactions. This feature, along with a highly porous sandwiched skin layer, makes this architecture superior to conventional powder catalysts or other structured catalyst forms like monoliths. Alumina hollow fibers are prepared by the modified phase inversion method and characterized for their pore size and distribution. Ni metal nanoparticles are uniformly deposited in the Al2O3 hollow fibers to prepare a Ni/Al2O3 catalyst and tested for the CO2 methanation reaction. Suitable reactor and catalyst loading methods are designed and optimized to achieve higher CO2 to methane conversion in a temperature range of 225 to 400 degrees C. The alpha-alumina phase, which is usually reported to be a poor support for Ni in CO2 methanation in the conventional fixed bed configuration, showed high activity when modulated as hollow fibers. Also, the selectivity to CH4 is enhanced and minimal CO formation is observed. The kinetic rate expressions are simulated for the prediction of methane and CO gas evolution at the outlet with temperature. The experimental results for the gas composition are in good agreement with the model predictions. The advantage of such a module reactor is explained based on the mass transfer limitations and consequently the reaction time constants arrived at from the predicted gas compositions.

Deciphering the role of chemisorbed CO in CO2 methanation: kinetic and mechanistic investigation over monometallic (Ru) and bimetallic (Ru-Ni) catalysts - Dongapure, Pavan; Tekawadia, Jyoti; Naidu, V. Satyam; Devi, R. Nandini (Catalysis Science & Technology, 2024)
Supported metal catalysts have made prominent contributions to CO2 mitigation through conversion into useful chemicals. However, intermediates and mechanisms involved in this process remain ambiguous. Herein, we present the kinetics, mechanistic route and impact of chemisorbed CO in CO2 methanation on Ru/gamma-Al2O3 and Ru-Ni/gamma-Al2O3 catalysts. Both the catalysts show minimal variation in adsorbed species on changing the duration of reduction, as confirmed through in situ IR spectroscopy. A notable observation is that the adsorbed CO exhibits a red shift at a longer reduction time and a more reactive nature on the Ru/gamma-Al2O3 surface. Conversely, stable bridged CO mode is detected on Ru-Ni/gamma-Al2O3 under similar conditions, leading to catalyst poisoning in all instances. This indicates that pre-reduction duration does not have much effect on the surface but interference of CO has more effect at lower concentrations of reactant gases. In situ XRD analysis reveals limited changes in the metallic or mixed oxide species during these conditions. Reaction kinetic analysis showed that Ru-Ni/gamma-Al2O3 has better rate performance at higher concentrations of CO2, whereas Ru/gamma-Al2O3 exhibits better rate performance at lower concentrations. The activation energy was found to be 74.07 kJ per mole for Ru/gamma-Al2O3 and 89.38 kJ per mole for Ru-Ni/gamma-Al2O3. The turnover frequency (TOF) is directly proportional to the rate of formation of methane.